REGULATION OF NEUROPEPTIDE Y, VASOACTIVE INTESTINAL PEPTIDE AND GALANIN BY INSULIN IN RATS: Regulation of Neuropeptide Y - Irshad, Tariq Mahmood; Khan, Farooq Ahmed (Pakistan Armed Forces Medical Journal, 2009)
Objective: To study the regulation of neuropeptide Y, vasoactive intestinal peptide and galanin by insulin in rats. Study Design: Experimental study. Place and Duration of Study: The study was conducted at the department of Metabolic Medicine Hammersmith hospital, Royal Postgraduate Medical School, London for on year (1996-1997). Material and Methods: Tissue levels of neuro peptide Y (NPY) and vaso intestinal peptide (VIP) decreased of the intestine and pancreas in insulin infused rats. NPY was also decreased significantly in hypothalamus. No significant effect on NPY in brain stem and on VIP in hypothalamus was observed. Results: Galanin decreased significantly in intestine and hypothalamus. Galanin mRNA decreased to 57.78.8 percent of controls (p < 0.05) in intestine and 58.717.7 percent of controls in hypothalamus. Therefore insulin decreased the tissue levels of galanin by inhibiting its mRNA. Conclusion: It is concluded that NPY, VIP and galanin are negatively regulated by insulin. Actions of insulin on endocrine pancreas and central control of glucose homeostasis and food intake by insulin may be partly modulated through changes in these peptides. VIP acts synergistically with glucagon in the development of hyperosmolar coma in NIDDM patients. NPY and galanin increase ketone bodies formation and hyperphagia in diabetics and contribute in the development of diabetic ketoacidosis and obesity.